Plant and Microalgae Derived Peptides Are Advantageously Employed as Bioactive Compounds in Cosmetics - Apone, Fabio; Barbulova, Ani; Colucci, Maria Gabriella (Frontiers in Plant Science, 2019)
Bioactive peptides are specific protein fragments that are physiologically important for most living organisms. It is proven that in humans they are involved in a wide range of therapeutic activities as antihypertensive, antioxidant, anti-tumoral, anti-proliferative, hypocholesterolemic and anti-inflammatory. In plants, bioactive peptides are involved in the defence response, as well as in the cellular signalling and the development regulation. Most of the peptides used as ingredients in health-promoting foods, dietary supplements, pharmaceutical and cosmeceutical preparations are obtained by chemical synthesis or by partial digestion of animal proteins. This makes them not fully accepted by the consumers because of the risks associated with solvent contamination or the use of animal derived substances. On the other hand, plant and microalgae derived peptides are known to be selective, effective, safe and well tolerated once consumed, thus they have got a great potential for use in functional foods, drugs and cosmetic products. In fact, the interest in the plant and microalgae derived bioactive peptides is rapidly increasing and in this review we highlight and discuss the current knowledge about their studies and applications in the cosmetic field.